Measuring the phase shifts of quasi-harmonic signals - Ignatjev, V.K.; Nikitin, A.V.; Yushanov, S.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2013)
A high-precision digital method of measuring the phase shifts is proposed for the signals whose parameters vary slowly over the time period equal to the discretization period but are able to change significantly over the entire measurement interval.